(2600+4600)-3.x=1200
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
( 2600 + 6400 ) - 3 . x = 1200
9000 -3x =1200
3x = 9000-1200= 7800
x = 7800 : 3
x =2600
( 2600 + 6400 ) - 3 . x = 1200
=> 9000 -3x =1200
=> 3x = 9000-1200= 7800
=> x = 7800 : 3
=> x = 2600
(2600 + 6400) - 3.x = 1200
9000 - 3.x = 1200
3.x = 9000 - 1200
3.x = 7800
x = 7800 : 3
x = 2600
(2600+6400)-3x=1200
10 000-3x=1200
3x=9000-1200
3x=7 800
x=7800/3
x=2600
\(\left(2600+6400\right)-3.X=1200\)
\(9000-3.X=1200\)
\(3.X=9000-1200\)
\(3.X=7800\)
\(X=7800:3\)
\(X=2600\)
(2600+6400)-3xX=1200
⇒ 9000-3xX=1200
⇒ 3xX=9000-1200=7800
⇒ X=7800:3=2600
⇒ X=2600
(2600+6400)-3.x=1200
=>9000-3.x=1200
=>3.x=9000-1200
=>3.x=7800
=>x=7800:3
=>x=2600
a) 2600 + X : 4 = 3845 X : 4 =3845-2600 X : 4 =1245 X = 1245x4 X = 4980 b) X x 3 +1200 =3600 X x 3 =3600-1200 X x 3 =2400 X =2400:3 X =600
( 2600+6400 ) - 3. x = 1200
9000 -3 . x = 1200
3 . x = 9000-1200
3 . x = 7800
x = 7800 : 3
x = 2600
3.x=(2600+4600)-1200
3.x= 7200 - 1200
3.x= 6000
x= 6000 : 3
x= 2000
Lớp 6 mà k làm dc bài ni ak